Correlation Of Leg Explosive Power With Shooting Quality In Soccer Games - Marsuna Marsuna; Muhtar Asshagab; Oril Saputra (STAMINA, 2026)
This study aims to determine the correlation between leg explosive power and shooting quality in soccer games. The research method uses a quantitative approach with a correlational design. The research sample consisted of 30 male students selected through a purposive sampling technique. The instruments used included a standing broad jump test to measure leg explosive power and a shooting test to assess shooting quality. The results of the descriptive analysis showed an average leg explosive power of 2.079 meters and an average shooting quality of 1.027. The normality test obtained a significance value of 0.46 for explosive power and 0.65 for shooting, which indicates that both variables are normally distributed. The linearity test produced a Sig. value of 0.724 > 0.05, so the relationship between the variables is declared linear. The results of the correlation test using SPSS showed a value of r = 0.678 with Sig. 0.000 < 0.05, which means there is a strong and significant relationship between leg explosive power and shooting quality. Thus, it can be concluded that the higher the leg explosive power, the better the shooting quality in soccer games